Raising Community Awareness About The Importance Of Education Through Educational Seminars In Babakanmulya Village: Meningkatkan Kesadaran Masyarakat Tentang Pentingnya Pendidikan Untuk Masa Depan Melalui Seminar Pendidikan Di Desa Babakanmulya Kabupaten Kuningan - Farrel, Muhammad; Huda, Uu Nurul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The Babakanmulya community's low awareness of the importance of education has led to a high dropout rate, mainly influenced by economic conditions and patriarchal culture. This service program uses a Participatory Action Research (PAR) approach through three stages: planning (FGD), implementation (educational seminar), and impact evaluation. The partners in this program are the Babakanmulya Village Government and local community leaders. The seminar was attended by more than 50 participants, showed high enthusiasm, and increased understanding of the importance of education and access to scholarships. There was a change in the way the community, especially parents, viewed education. There were further initiatives from the village to support formal and non-formal education.